2017
DOI: 10.1167/iovs.16-21347
|View full text |Cite
|
Sign up to set email alerts
|

Iris Malformation and Anterior Segment Dysgenesis in Mice and Humans With a Mutation in PI 3-Kinase

Abstract: PurposeTo determine the ocular consequences of a dominant-negative mutation in the p85α subunit of phosphatidylinositol 3-kinase (PIK3R1) using a knock-in mouse model of SHORT syndrome, a syndrome associated with short stature, lipodystrophy, diabetes, and Rieger anomaly in humans.MethodsWe investigated knock-in mice heterozygous for the SHORT syndrome mutation changing arginine 649 to tryptophan in p85α (PIK3R1) using physical examination, optical coherence tomography (OCT), tonometry, and histopathologic sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Apoptosis of lens epithelial cells was known to be an early event in the development of many types of cataracts (Li and Spector, 1996;Shiels and Hejtmancik, 2019). Previous studies suggested that the dominant-negative mutation of Pik3r1 could lead to cataract in human and mice (Solheim et al, 2017), and the activation of PI3K/AKT signaling pathway by circRNA HIPK3 or melatonin could inhibit apoptosis of HLECs (Bai et al, 2013;Cui et al, 2020). Notch2 was proved to be inhibited in the formation of age-related cataract (Fan et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis of lens epithelial cells was known to be an early event in the development of many types of cataracts (Li and Spector, 1996;Shiels and Hejtmancik, 2019). Previous studies suggested that the dominant-negative mutation of Pik3r1 could lead to cataract in human and mice (Solheim et al, 2017), and the activation of PI3K/AKT signaling pathway by circRNA HIPK3 or melatonin could inhibit apoptosis of HLECs (Bai et al, 2013;Cui et al, 2020). Notch2 was proved to be inhibited in the formation of age-related cataract (Fan et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…10,15 In addition, due to insulin and growth factor resistance, mice heterozygous for this mutation exhibit many phenotypic traits observed in human patients including partial lipodystrophy, severe insulin resistance, growth retardation, and iris malformation similar to SHORT Syndrome patients. 1,15,16 In addition to the classical role of the PI3K regulatory subunits acting to couple tyrosine phosphorylation events to increase PI3K catalytic activity, monomeric p85, that is, p85 that is not in complex with the p110 catalytic subunit, has been shown to have a role in regulating activity of Jun N-terminal kinase (JNK) and the phosphatase and tensin homolog, PTEN. 3,[17][18][19][20] We and others have demonstrated that monomeric p85α interacts with XBP-1s in an endoplasmic reticulum (ER) stress-dependent manner and that this interaction facilitates the nuclear translocation of XBP-1s, thus, facilitating induction of the ER stress response.…”
Section: Introductionmentioning
confidence: 99%
“…Patient fibroblasts and mouse cell lines that are heterozygous for the mutant allele exhibit a significant impairment in insulin and growth factor‐dependent activation of PI3K and the activation of its downstream target, AKT 10,15 . In addition, due to insulin and growth factor resistance, mice heterozygous for this mutation exhibit many phenotypic traits observed in human patients including partial lipodystrophy, severe insulin resistance, growth retardation, and iris malformation similar to SHORT Syndrome patients 1,15,16 …”
Section: Introductionmentioning
confidence: 99%
“…We recently created knock-in (KI) animals heterozygous for the R649W mutation (24). Similar to affected patients, these mice exhibit a reduction in body weight and length, ocular abnormalities, partial lipodystrophy, and insulin resistance (24,26). Mice with the heterozygous R649W mutation also show reduction in adipose fat mass due largely to a reduction in adipocyte size.…”
mentioning
confidence: 99%